2008
DOI: 10.1007/s11136-008-9336-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life following blind rehabilitation

Abstract: Purpose-The purpose of this study was to investigate the effect of residential blind rehabilitation on patients' vision targeted health-related quality of life (HRQOL) and general physical and mental function.Methods-The National Eye Institute 25-item Visual Function Questionnaire (NEI VFQ) plus appendix questions, the 12 item Short-Form Health Survey (SF-12), Hope Scale and Coopersmith self-esteem inventory were administered to 206 legally blind veterans prior to their entering a residential (in-patient) blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 35 publications
1
40
2
Order By: Relevance
“…88 A greater improvement in almost all subscales of NEI-VFQ 25 was seen at 2 compared with 6 months, but the difference was small (effect size 0.59 at 2 months and 0.55 at 6 months). Kuyk et al found a larger effect size than Stelmack et al, who also evaluated a Veterans' Affairs inpatients service using the same outcome measure, but followed up immediately after the end of rehabilitation.…”
Section: Figure 2 About Herementioning
confidence: 83%
See 4 more Smart Citations
“…88 A greater improvement in almost all subscales of NEI-VFQ 25 was seen at 2 compared with 6 months, but the difference was small (effect size 0.59 at 2 months and 0.55 at 6 months). Kuyk et al found a larger effect size than Stelmack et al, who also evaluated a Veterans' Affairs inpatients service using the same outcome measure, but followed up immediately after the end of rehabilitation.…”
Section: Figure 2 About Herementioning
confidence: 83%
“…Kuyk et al showed a moderate increase in vision-related QoL (NEI-VFQ 25) after a very intensive inpatient service treating male veterans who were legally blind. 88 The composite score effect size was 0.59 and 0.55 at 2 and 6 months follow-up respectively. The near vision subscale effect size was greatest (1.49 and 1.44 effect size at 2 and 6 months respectively).…”
Section: Effect Of Rehabilitation On Vision-related Quality Of Lifementioning
confidence: 89%
See 3 more Smart Citations